THE INTERPLAY OF INTERNAL CONTROL, WHISTLEBLOWING, GOOD GOVERNANCE, AND ORGANIZATIONAL CULTURE IN FRAUD PREVENTION: THE MODERATING ROLE OF INFORMATION TECHNOLOGYFraud remains a persistent organizational challenge that undermines financial stability, ethic (Lex localis - Journal of Local Self-Government, 2025)
Fraud remains a persistent organizational challenge that undermines financial stability, ethical conduct, and public trust. This study investigates the determinants of fraud prevention by examining the direct effects of internal control systems, whistleblowing mechanisms, good governance, and organizational culture, while assessing the moderating role of information technology (IT). Using a Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, empirical data were analyzed to test both direct and moderated relationships. The findings reveal that internal control systems, whistleblowing mechanisms, and organizational culture significantly enhance fraud prevention, whereas good governance demonstrates a negligible direct effect. Importantly, IT was found to strengthen the relationship between internal control systems and fraud prevention but paradoxically weakened the effectiveness of whistleblowing systems. The moderating effects of IT on governance and organizational culture were statistically insignificant, indicating that cultural and normative dimensions of governance require institutional embedding beyond technological tools. Theoretically, this study contributes to the socio-technical systems perspective by highlighting how organizational and technological dimensions jointly influence fraud prevention. Practically, the findings suggest that organizations should prioritize IT-enabled control systems, redesign whistleblowing platforms to foster trust, and embed governance values and ethical culture into daily operations. These insights are relevant for regulators, policymakers, and practitioners seeking to design more effective anti-fraud frameworks in an era of rapid digital transformation.